An examination of the hopelessness levels and self-esteem of parents with special needs children - Nazan Kaytez; Bayram Deleş; Neriman Aral (BMC Psychology)
Abstract Every parent dreams of having a child with typical development. However, parents may have a child with special needs due to any reason that occurs before or after birth. Having a child with special needs is a difficult situation to accept. This problematic situation may be associated with parents’ self-esteem and hopelessness levels. This study aimed to determine the variables related to parents’ self-esteem and hopelessness levels and to examine the relationship between self-esteem on hopelessness levels. Method The study was conducted in a province in the north of Turkey. The study group consisted of 200 parents whose children received education in a special education and rehabilitation center in this province and voluntarily agreed to participate. The “Personal Information Form,” “Beck Hopelessness Scale,” and “Rosenberg Self-Esteem Scale” were used as data collection tools. The research data were analyzed using regression analysis. Results As a result of the study, it was determined that self-esteem was associated with and significantly predicted the hopelessness level of parents by 17%. Accordingly, as parents’ self-esteem increased, their hopelessness levels decreased. In addition, a significant relationship was found between parents’ self-esteem and socioeconomic level, the status of wanting to have children again, the type and degree of the child’s disability, and between hopelessness levels and the status of wanting to have children again, educational level, socioeconomic level, age of the child and the degree of disability. Conclusions As parents’ self-esteem increased, their hopelessness levels decreased. As socioeconomic and educational levels decreased, parents’ self-esteem decreased and hopelessness levels increased. Parents who wanted to have children again and had children with mild disabilities had higher self-esteem and lower levels of hopelessness.